Busan Biennale : contemporary art exhibition, sea art festival, Busan sculpture project. - Busan Biennale Organizing Committee, Busan (Busan (Korea) : Busan Biennale Organizing Committee, 2003)
Aquilizan, Alfredo & Isabel ; Rawanchaikul, Navin ; Shimabuku ; Poirier, Anne & Patrick ; Erlich, Leandro ; Byun, Dae-Yong ; Kim, Sung-min ; Kim, Tae-in ; Kim, Tae-Hyun ; Lee, Dong-Ju ; Sung, Tae-Kwan ; Choi, Pyung-Gon ; Park, Dong-Sub ; Seo, Sang-Ho ; Kuckuck, Henner ; Kim, Young-Won ; Ney, Bertrand ; Kim, Won-Kyung ; Tsukawaki, Jun ; Nolden, Rolf ; Krystufek, Elke ; Navridis, Nikos ; Cunha, Alexandre da ; Shon, Jeung-Eun ; Mthethwa, Zwelethu ; Moon, Beung-Tak ; Pyo, In-Suk ; Park, Sang-Ho ; Kim, Yong-Sub ; Meier, Hubert ; Oveis Saheb Djawaher ; Hashimoto, Yoshimi ; Ramey, Don ; Eller, Thomas ; Borek, Malgorzata ; Eyre, Janieta ; Semmes, Beverly ; Park, Hyun-Ki ; Cheong, Jin-Yun ; Takada, Satoru ; Nivèse
over Busan Biennale 2004, 2002, 2000, 1998
Engels
boek